2020
DOI: 10.3390/su12062334
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-Cell Electric Vehicles: Plotting a Scientific and Technological Knowledge Map

Abstract: The fuel-cell electric vehicle (FCEV) has been defined as a promising way to avoid road transport greenhouse emissions, but nowadays, they are not commercially available. However, few studies have attempted to monitor the global scientific research and technological profile of FCEVs. For this reason, scientific research and technological development in the field of FCEV from 1999 to 2019 have been researched using bibliometric and patent data analysis, including network analysis. Based on reports, the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…Consequently, the low availability of vehicles then reduces the rationale for market investors and policymakers to commit to rolling out refuelling infrastructure [53,54]. Meanwhile, the supply of vehicles may also be impeded by technological difficulties in mass producing components like fuel cells and hydrogen tanks [55] or the lack of alternatives to expensive materials used in these [23,49,56]. The absence of strong environmental policies forcing investments in ZEV technologies will also likely hamper the growth of hydrogen mobility.…”
Section: Description Of Four Categories 221 Supply-side Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the low availability of vehicles then reduces the rationale for market investors and policymakers to commit to rolling out refuelling infrastructure [53,54]. Meanwhile, the supply of vehicles may also be impeded by technological difficulties in mass producing components like fuel cells and hydrogen tanks [55] or the lack of alternatives to expensive materials used in these [23,49,56]. The absence of strong environmental policies forcing investments in ZEV technologies will also likely hamper the growth of hydrogen mobility.…”
Section: Description Of Four Categories 221 Supply-side Factorsmentioning
confidence: 99%
“…The maturity, reliability and performance of core components in vehicles (e.g., fuel cell stacks and fuel tanks) and the ability to mass-produce these. [9,23,28,49,55,56,62] Table 1. Cont.…”
Section: Supply Of Vehiclesmentioning
confidence: 99%
“…The other approach involves focusing on the value chain of the hydrogen economy from an infometrics perspective (bibliometrics and scientometrics), which is based on a paper and/or patent [1, [32][33][34][35][36], or from the evaluation of green energy sources [37][38][39]. Some scholars have presented future research directions by investigating the evolution of hydrogen research regarding production [1, 33,40,41], storage/transportation [33,34,42], and utilization [35,36,[43][44][45][46][47], as discussed in Section 1.1.2. Several studies have revealed the emergence of biohydrogenation, photocatalysis, and water splitting as methods for producing hydrogen from renewable energy sources [1, 33,40,41], thus revealing prominent international cooperation among different countries/regions and institutions [42].…”
Section: Limitations Of the Research On The Hydrogen Economy And Significance Of A Systematic Framework For Implementing The Strategymentioning
confidence: 99%
“…HFCs are currently one of the least used types of alternative fuels, but they are destined to catch up. Accordingly, research production in this field is significantly growing up and reaching a maturity [259]. A development of HFC Vehicle (HFCV) technology is represented by its battery hybridization called Plug-in Hydrogen Fuel Cell Hybrid Vehicles (PHFCVs), which are advantageous when compared to traditional hybrid vehicles because they use a single electric motor.…”
Section: Hydrogen Fuel Cellsmentioning
confidence: 99%